Navigating the Kingdom of Night - T Matthews, Amy (University of Adelaide Press, 2013)
In 2011, Amy T Matthews published End of the Night Girl, a novel which engages creatively with questions of identity politics and the ethics of fictionalising the Holocaust. Navigating the Kingdom of Night is a critical exegesis in which the author contextualises End of the Night Girl in terms of the critical debate surrounding Holocaust fiction.